Answer:
The solution of x are [tex]x=-1+\sqrt{17}[/tex] and [tex]x=-1-\sqrt{17}[/tex]
Step-by-step explanation:
We are given [tex]x^2+2x+1=17[/tex]
We need to solve for x.
First we move 16 to left side ans then factor it
[tex]x^2+2x+1-17=0[/tex]
[tex]x^2+2x-16=0[/tex]
Using quadratic formula,
[tex]x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
[tex]x=\dfrac{-2\pm\sqrt{4+64}}{2}[/tex]
[tex]x=\dfrac{-2\pm2\sqrt{17}}{2}[/tex]
[tex]x=-1\pm\sqrt{17}[/tex]
Thus, The solution of x are [tex]x=-1+\sqrt{17}[/tex] and [tex]x=-1-\sqrt{17}[/tex]